2012
DOI: 10.1038/srep00682
|View full text |Cite
|
Sign up to set email alerts
|

Large-area high-throughput synthesis of monolayer graphene sheet by Hot Filament Thermal Chemical Vapor Deposition

Abstract: We report hot filament thermal CVD (HFTCVD) as a new hybrid of hot filament and thermal CVD and demonstrate its feasibility by producing high quality large area strictly monolayer graphene films on Cu substrates. Gradient in gas composition and flow rate that arises due to smart placement of the substrate inside the Ta filament wound alumina tube accompanied by radical formation on Ta due to precracking coupled with substrate mediated physicochemical processes like diffusion, polymerization etc., led to graphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
115
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 58 publications
10
115
0
1
Order By: Relevance
“…A similar situation due to reactions of the water-soluble PEIE with moisture in air was also found in the case of electron-doped graphene shown in Fig. 8(b), where the spectrum of the binding energy of C-1s core electron exhibited an increase of the C-C¼O component (at 288.7 eV) 21,22 with time plus a small trace of the C-OH component (at 285.7 eV). The relevant chemical reaction here may involve either…”
Section: Results and Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…A similar situation due to reactions of the water-soluble PEIE with moisture in air was also found in the case of electron-doped graphene shown in Fig. 8(b), where the spectrum of the binding energy of C-1s core electron exhibited an increase of the C-C¼O component (at 288.7 eV) 21,22 with time plus a small trace of the C-OH component (at 285.7 eV). The relevant chemical reaction here may involve either…”
Section: Results and Analysissupporting
confidence: 76%
“…As shown in Fig. 8(a) for hole-doped monolayer graphene in air, the binding energy of the C-1s core electron appeared to increase with time up to 0.15 eV after 30 days, which was accompanied by increasing strengths of the sp 2 hybridized C-OH (at 285.7 eV) and the sp 3 C-O (at 286.6 eV) components of a comparable binding energy 21,22 as indicated by the arrow. The formation of the C-OH and C-O bonds may be understood as the result of the reaction of H 3 O þ with graphene, leading to either H 3 2À .…”
Section: Results and Analysismentioning
confidence: 86%
“…In recent years, there has been great improvement on the synthesis of high quality graphene using various methods, including chemical vapor deposition (CVD) grown graphene on different metal foils [137][138][139][140][141][142][143][144][145], and synthesis of epitaxial graphene on SiC substrates [146][147][148][149]. Moreover, recent low-cost rollto-roll [150,151] and large-area [146,152] synthesis methods have reduced the cost of graphene.…”
Section: Nw Growth On Graphenementioning
confidence: 99%
“…Numerous functional graphene materials have now been synthesized using different structural motifs including metal-organic frameworks, polymers, biomaterials, organic crystals, and inorganic nanostructures. Several synthetic approaches, such as chemical vapor deposition (CVD), [5][6][7] micromechanical exfoliation, [ 5,8 ] epitaxial growth on SiC, [ 8,9 ] solution route wet chemical exfoliation, [ 10 ] sonochemical liquid-phase exfoliation, [ 8,11 ] of Gly·HSO 4 is equal to the total molecular mass of starting glycine and H 2 SO 4 ), being low-cost, and environmentally friendly, and has been applied previously for organocatalysis. [35][36][37] To date, it has not been applied in the electrochemical processing of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Within this broader processing regime the use of ionic liquids [23][24][25] are of particular interest due to their suitability as electrolytes. Previously, Liu et al [ 23 ] and Lu et al [ 24 ] have demonstrated the preparation of graphene via the electrochemical intercalation of PF 6 − and BF 4 − anions into graphite layers using alkylimidazolium hexafl uorophosphate (RIMPF 6 ) and alkylimidazolium tetrafl uoroborate (RIMBF 4 ) ionic liquids. Ionic liquids have several merits, including negligible vapor pressure, low toxicity, high chemical and thermal stability, and ease of availability.…”
mentioning
confidence: 99%